Controller synthesis for negative imaginary systems: a data driven approach. Issue 12 (1st August 2016) - Mabrok, Mohamed A.; Petersen, Ian R.
Abstract : The negative imaginary (NI) property occurs in many important applications. For instance, flexible structure systems with collocated force actuators and position sensors can be modelled as negative imaginary systems. In this study, a data‐driven controller synthesis methodology for NI systems is presented. In this approach, measured frequency response data of the plant is used to construct the controller frequency response at every frequency by minimising a cost function. Then, this controller response is used to identify the controller transfer function using system identification methods.